G433(P) Lupus and you: developing a workshop for young people with lupus and their families. (24th May 2017) - Wilson, ERH; Lythgoe, H; Smith, E; Preston, J; Beresford, MW
Abstract : Background: Lupus is a severe, autoimmune disease that is very rare in children and young people. As a regional service and the UK's only 'Centre of Excellence for Childhood Lupus', our patients live across a large geographical area. Many have never met another young person with lupus and report how isolating this could feel. The psychological impact of chronic illnesses are well-known and potentially debilitating. Aims: We aimed to develop a series of day-long multidisciplinary workshops for young people with lupus and their families. As part of a stepped-care model of psychological support, we wanted to intervene proactively to promote resilience and coping as well as responding to an individual's difficulties as they arouse. Method: 7 families participated in the first workshop which focused on managing fatigue and research participation. Fatigue was highlighted as a frequent area of concern by young people and their parents when completing a routinely preclinic screening tool. All participants completed a range of standardised psychological measures as well as a workshop feedback form. Results: Participant participated in exercises designed to encourage sharing of experiences as well hearing examples of strategies to manage fatigue. High levels of fatigue were identified among lupus patients (mean score on the fatigue severity scale 5.1 (range 4–5.8) where people scoring above 3 points are considered to suffer with fatigue). Young people and their families reported increased confidence in managing fatigue when pre- and post-workshop data were compared. Information about local and national research in paediatric lupus was shared in an interactive session. There was considerable variation in the extent to which young people were coping with lupus. Attendees reported finding the workshop helpful and convenient to attend. Support for siblings, medication, and symptom knowledge were identified as potential future workshop topics. Conclusion: The 'Lupus and You' workshop allowed young people and their families to share experiences of managing lupus, to develop supportive relationships while also developing resilience and practical strategies for living life fully despite lupus.